PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS LITERASI PADA KETERAMPILAN MEMBACA PESERTA DIDIK KELAS V SDN 09 KOTO BARU - Amar Salahuddin; Estuhono; Nanda Ananta (STKIP Subang, 2024)
This research was motivated by the lack of teaching materials in the learning process, especially in making teaching materials. The teaching materials used in this school still use textbooks and worksheets as the teaching materials used. This school needs creative teaching materials that can attract students' attention in the learning process, especially when reading, while students like to learn using interesting learning media so that when reading, not only text, students also enjoy seeing pictures, in this school lack of interesting learning media. In this research, researchers want to develop LKPD. This research aims to make LKPD attractive and creative. Types of research and development Research and Development (R&D). The model used in this research is the 4-D model consisting of 4 stages, namely the definition stage (Define), the design stage (Design), the development stage (Develop), the deployment stage (Dessiminate). The types of data collection taken in this research were interview sheets, validity, practicality and effectiveness instruments. Data collection techniques use observation, interviews, questionnaires and documentation techniques. Data analysis techniques include validity, practicality and effectiveness data analysis. The validation results by graphics experts were 84% in the very valid category, content/material experts 88.88% in the valid category, linguists 85.71% in the very valid category. the results of the questionnaire data analysis, the responses of teachers and class IV students were 100% in the very practical category. The results of effectiveness data analysis through test questions with an average score of 89.47% in the effective category.